Mapping the effective coverage of modern contraceptive services in Ethiopia - Samrawit Birhanu Alemu; Molla Yigzaw Birhanu; Mekdes Tamiru Yizengaw; Melaku Birhanu Alemu (PLoS ONE, 2025)
Introduction Modern contraceptive services are vital for reducing maternal and infant morbidity and mortality. However, in Ethiopia, the effective coverage (quality-adjusted coverage) of these services remains low and varies significantly across administrative regions. Despite these disparities, the spatial distribution of effective coverage is not well understood, limiting the ability to implement targeted interventions in areas with low coverage. Methods We used the 2019 Ethiopia Demographic Health Survey (EMDHS) to estimate the crude coverage of modern contraceptive services. In addition, we used the 2021–2022 Ethiopia Services Provision Assessment (ESPA) to estimate the quality of modern contraceptive services provision. The two datasets were linked using the Euclidean buffer link method to estimate the effective coverage. The effective coverage was calculated as the product of coverage and quality estimates for each health facility. The geospatial estimates were presented using the coordinates from the ESPA survey. We analysed the spatial distribution of modern contraceptive coverage using ArcGIS 10.7 software. The Global Moran’s I statistic was used to assess the spatial autocorrelation, while the Getis-Ord Gi* statistic was used to identify high and low clusters. The Kriging interpolation method was used to estimate effective coverage in unsampled areas based on sampled clusters. Results The effective coverage of modern contraceptive services in Ethiopia was 20% (95% confidence interval (CI): 19.87, 21.82), which was notably lower than the crude coverage of 30% (95% CI: 28.93, 31.62), resulting in a gap of 10% points. The spatial distribution analysis showed that effective modern contraceptive coverage had a significant spatial autocorrelation in Ethiopia, with the Global Moran’s index value of 1.92 (p-value < 0.001). The effective coverage of modern contraceptive services was notably higher in Central Amhara, Western Amhara, Central Oromia, the western part of South West Ethiopia, Sidama, and the northern part of the Southern Nations, Nationalities, and Peoples (SNNP). Addis Ababa, western Amhara, northeast Benishangul-Gumuz, eastern part of South West Ethiopia, north SNNP, Sidama, and northern and central Oromia had hotspots for effective coverage of modern contraceptives. On the other hand, Afar, western Gambela, western Oromia, western Benishangul-Gumuz, Dire Dawa, Harari and Somali had cold spots for effective coverage of modern contraceptive services. Conclusions There is a significant spatial variation in the effective coverage of modern contraceptive services in Ethiopia. Afar, western Gambela, western Oromia, western Benishangul-Gumuz, Dire Dawa, Harari, and Somali had low effective coverage. To enhance equitable access, policymakers should prioritise interventions such as improving healthcare infrastructure and strengthening service delivery to improve modern contraceptive coverage and quality in underserved areas.